Developing classification criteria for discoid lupus erythematosus: an update from the World Congress of Dermatology 2015 meeting - Scott A. Elman, AB; Filippa Nyberg, MD; Fukumi Furukawa, MD; Mark Goodfield, MD; Minoru Hasegawa, MD; Branka Marinovic, MD; Jacek Szepietowski, MD; Jan Dutz, MD, FRCPC; Victoria P. Werth, MD; Joseph F. Merola, MD, MMSc (Wolters Kluwer, 2016)
Currently, no standardized classification criteria exist for cutaneous lupus erythematosus. With increased interest in studying cutaneous lupus erythematosus, specifically discoid lupus erythematosus, it is our aim to apply previously adopted methods from rheumatology to dermatologic diseases to develop feasible, validated, and standardized classification criteria useful in both academic and community practice. Here we report the progress to date to define discoid lupus erythematosus using clinical, histopathologic, and serologic features by means of a Delphi method-using a series of iterative questionnaires sent to expert stakeholders. We present specific updates from the World Congress of Dermatology 2015 meeting, at which a nominal group of expert stakeholders met to discuss the results of round 1 of the Delphi process to further clarify and harmonize specific classification items for inclusion into round 2. Key words: Discoid Lupus Erythematosus, Cutaneous Lupus Erythematosus, Lupus, Connective Tissue Diseases, Delphi method, classification criteria, World Congress of Dermatology